A Five‐Step Total Synthesis of Parvistone B. Issue 12 (9th August 2016) - Ramesh, Perla
Abstract: The first total synthesis of a naturally occurring styryllactone secondary metabolite parvistone B has been achieved in five steps with an overall yield of 67 % from readily available trans ‐cinnamaldehyde. It exhibits cytotoxicity against different human tumour cell lines. Key features of our synthetic strategy include Maruoka asymmetric allylation, Sharpless epoxidation, ring‐closing metathesis, and regioselective epoxide ring‐opening. This synthetic strategy constitutes a step economical, atom economical and protecting group‐free total synthesis. Abstract : The first total synthesis of a bioactive styryllactone secondary metabolite parvistone B has been achieved in five steps with an overall yield of 67 % from readily available trans ‐cinnamaldehyde The efficient synthesis features a successful protecting group‐free strategy, with desirable step‐ and atom‐ economy.